An overview of small hydropower plants in Colombia: Status, potential, barriers and perspectives. (October 2015) - Morales, Sergio; Álvarez, Camilo; Acevedo, Cesar; Diaz, Carlos; Rodriguez, Miguel; Pacheco, Leonardo
Abstract: The negative environmental impacts associated to the use of large hydropower plants have helped to focus the attention on small-scale plants, which reduce these impacts considerably. In Colombia, there is an important potential for the implementation of both, large and small-scale hydropower projects, which has been exploited mostly in large plants. Accordingly, the purpose of this paper is to analyze the present situation of small hydropower (SHP) in Colombia, including current installed capacity and existing potential of hydro-energy resources. In addition, the paper presents the barriers that hinder the proliferation of SHP in the country, the main perspectives for future developments and the corresponding conclusions of the analysis performed.